Yield and storability of onion (Allium cepa L.) as affected by varying levels of irrigation (Bangladesh Journal of Agricultural Research, 2010)
Bulb yield and storability of onions (cv. BARI Piaj-1) was studied against five levels of irrigation viz., no irrigation, irrigation at 10, 15, 20, and 30 days interval. Yield and storage losses were increased gradually with increasing number of irrigation. The highest yield of onion was obtained with a total of six irrigations at 10 days interval and it was at par with treatment that received four irrigations at 15 days intervals. Losses due to rotting, sprouting, and physiological weight loss were found higher in irrigated treatments. After six months of storage (from 1st week of April to 1st week of October), the maximum cumulative weight loss (56.72%) was recorded in onions irrigated at 10 days interval, while the minimum (46.80%) was recorded in non-irrigated onions. Keywords: Storability; onion bulb; irrigation; storage losses.DOI: 10.3329/bjar.v35i2.5887Bangladesh J. Agril. Res. 35(2) : 247-255, June 2010